Blood-brain barrier–penetrating siRNA nanomedicine for Alzheimer’s disease therapy - Zhou, Yutong; Zhu, Feiyan; Liu, Yang; Zheng, Meng; Wang, Yibin; Zhang, Dongya; Anraku, Yasutaka; Zou, Yan; Li, Jia; Wu, Haigang; Pang, Xiaobin; Tao, Wei; et al. (Science Advances, 2020)
Glycosylated “triple-interaction” stabilized siRNA nanomedicine ameliorated AD neuropathology by targeting BACE1. Toxic aggregated amyloid-β accumulation is a key pathogenic event in Alzheimer’s disease (AD), which derives from amyloid precursor protein (APP) through sequential cleavage by BACE1 (β-site APP cleavage enzyme 1) and γ-secretase. Small interfering RNAs (siRNAs) show great promise for AD therapy by specific silencing of BACE1. However, lack of effective siRNA brain delivery approaches limits this strategy. Here, we developed a glycosylated “triple-interaction” stabilized polymeric siRNA nanomedicine (Gal-NP@siRNA) to target BACE1 in APP/PS1 transgenic AD mouse model. Gal-NP@siRNA exhibits superior blood stability and can efficiently penetrate the blood-brain barrier (BBB) via glycemia-controlled glucose transporter-1 (Glut1)–mediated transport, thereby ensuring that siRNAs decrease BACE1 expression and modify relative pathways. Noticeably, Gal-NP@siBACE1 administration restored the deterioration of cognitive capacity in AD mice without notable side effects. This “Trojan horse” strategy supports the utility of RNA interference therapy in neurodegenerative diseases.